Psychological pressures and their relationship to basketball shooting accuracy among orphans - Salam, Sarah Hekmat Abdul; Khodair, Maryam Abdul Jabbar (Sulaimani Journal for Humanities, 2025)
This study explores the relationship between psychological stress and basketball shooting accuracy among orphaned middle school students, and how this affects their response and performance in physical education classes. Furthermore, the study addresses improving the educational environment and psychological support provided to orphaned students to enhance their learning and performance in this area. Through this study, we can discover the best ways to support orphaned students and alleviate the psychological stress that may affect their basketball shooting accuracy, thereby enhancing their educational experience and academic and personal success. The rationale for this research lies in understanding psychological stress and its impact on motor skills, as well as assessing performance levels through shooting accuracy tests. The importance of this research lies in identifying psychological stress and its relationship to basketball shooting accuracy among orphans. While sports can be beneficial for them as a means of self-expression, strengthening team spirit, and fostering optimism, it is also essential to provide them with appropriate psychological and social support to help them overcome these challenges and increase their performance in physical education classes. The research problem is formulated in the following question: Is there a relationship between psychological stress and basketball shooting accuracy among orphaned students?